Social Demographic Dimensions of Contraceptive Use in the Land of Papua: A Cross-Sectional Approach - Urip Tri Wijayanti; Evalina Franciska Hutasoit; Darojad Nurjono Agung Nugroho; Sri Sugiharti (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2024)
Background: The use of contraception is one of the efforts to prevent unwanted or mistimed pregnancies. Therefore, it has become a family planning program for motivating families to have ideal plans for pregnancies in time and with a desired number. However, although nationally, 58.7% of married women aged 15-49 years old used contraception in 2019, the percentage of contraceptive users remained the lowest in Papua, with only 13.7% of married women of the same age group using contraceptives in addition to 20% of the women having the unmet need for contraception. This study aims to analyze the determinants of the use of contraception in women of childbearing age in Papua Province.Method: This study employed data from the 2020 National Socioeconomic Survey (Susenas) with a cross-sectional approach. Respondents were 666,866 married women aged 10-54 years. Descriptive statistics and logistic regression analysis were performed using SPSS with a 95% confidence interval (p < 0.05) to express statistical significance.Results: Residence, educational status, pregnancy, employment, age at first marriage, number of children, cell phone ownership, and health insurance were significantly correlated with contraceptive use (p < 0.001). Residence in an urban area, junior high school education, pregnancy, marriage at less than 20 years of age, having more than two children alive, and ownership of a cell phone and health insurance were associated with an increased chance of using contraceptive methods among married women of reproductive age in Papua. The chance to use contraception was the highest for married pregnant women of reproductive age, and the women, in this case, were 35 times more likely to use contraceptives compared to unpregnant ones.